Relative Susceptibility Of Selected Maize Seed Varieties To The Maize Weevil (Sitophilus Zeamais Motschulsky) In Ghana - Acheampong, A. (University of Ghana, 2017)
Studies were carried out under ambient laboratory conditions of 25 ± 2°C and 70 ± 5% relative humidity to determine the relative susceptibility of eighteen maize seed varieties to attack by the maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae). The experiment was laid out in a Completely Randomized Design (CRD), with eighteen maize varieties replicated three times. Adult mortality, number of F1 progeny, weevil development time, susceptibility index, seed damage, seed weight loss, and weight of powder/frass produced were determined after storage period of three months. The susceptibility index was determined using Dobie’s formula and the varieties were classified into different reaction groups. The varieties exhibited varying degrees of susceptibility to S. zeamais attack. Only Aseda was regarded as resistant and TZE-Y POP STR as moderately resistant to S. zeamais. Kpari-Faako, Tintim, WACCI-M-1215, WACCI-M-1594 and Wang-Dataa were regarded as moderately susceptible to S. zeamais. However, Abontem, Bihilifa, Ewul-Boyu, Sanzal-Sima, TZE-I 17, WACCI-M-1205, WACCI-M-1508 and WACCI-M-1510 were regarded as susceptible varieties. Furthermore, Aburohemaa, Obaatanpa and Omankwa were regarded as highly susceptible to S. zeamais. Index of susceptibility (IS) had significant and positive association with the number of F1 progeny (r = 0.9, P<0.001), seed damage (r = 0.9, P<0.001), seed weight loss (r = 0.6, P<0.001), weight of frass produced (r = 0.9, P<0.001) and seed moisture content (r = 0.3, P<0.024). However, an inverse association existed between the IS and adult mortality (r = -0.4, P<0.005), median development period (r = -0.5, P<0.001) and seed germination (r = -0.7, P<0.001). The use of insect resistant varieties would offer a sustainable way of minimizing postharvest losses of seeds in storage especially for smallholder farmers who keep harvested grains for future use as food and seed.
Thesis (MPhil)
Keywords: Relative Susceptibility; Maize Seed Varieties; Maize Weevil (Sitophilus Zeamais Motschulsky); Ghana